Meningkatkan Hasil Belajar Siswa melalui Media Pembelajaran Multimedia Interaktif - Endang Sri Mureiningsih (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2014)
Social studies teaching aims to develop knowledge, understanding and analytical skills of the social conditions of the community in entering a dynamic social life, thus it is expected that social studies teaching can equip students to become democratic and responsible citizens. Less precise learning methods result in student learning outcomes that are not as expected. Therefore it is necessary to find interesting learning methods so that students more easily understand social studies subject matter that is always dynamic and developing, one of which is to use media. The problem of this research is whether using interactive multimedia media can improve student learning outcomes about the diversity of the Earth's Surface Forms with interactive multimedia media in class VII A semester I of SMP Negeri 2 Ampelgading Pemalang Regency, 2013/2014 Academic Year? This study uses 2 cycles. The results of this study indicate an increase in learning motivation from low to somewhat high, and an increase in learning outcomes of 47.43% from the average pre-cycle test results of 66.05 completeness 47.37%, cycle I increased to 72.36 with completeness 78 , 95% while the second cycle test averaged 81.08 completeness 94.74% then there was an increase.